1996
DOI: 10.1111/j.1398-9995.1996.tb02135.x
|View full text |Cite
|
Sign up to set email alerts
|

An electrical impedance technique for assessment of wheals

Abstract: In previous studies of the electrical impedance of the skin, we introduced a set of physical indices which could be used to distinguish between the cutaneous effects produced by different irritants and allergic contact reactions. In this study, wheals were induced in 10 allergic patients by performing prick tcsts on the forearm with the relevant allergen and histamine, respectively. Normal skin was used for control. The wheals were evaluated by visual scoring, laser Doppler, and electrical impedance. As expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Skin impedance has been used in many applications, for example classification (4) and quantification (5, 6) of skin irritations, differentiation between type I diabetics skin and reference skin (7), and evaluation of allergic reactions (8, 9).…”
mentioning
confidence: 99%
“…Skin impedance has been used in many applications, for example classification (4) and quantification (5, 6) of skin irritations, differentiation between type I diabetics skin and reference skin (7), and evaluation of allergic reactions (8, 9).…”
mentioning
confidence: 99%
“…In 10 allergic patients, on which prick tests of relevant antigens were performed on the volar forearm and compared to the controls, there were significant changes in the impedance parameters of the wheals, especially in the index related to the phase angle (Table 1). 19 The patterns of the statistically significant changes of the impedance indices differed from those obtained in contact skin reactions of both allergic and irritant types. Also, the results indicated that the allergic skin reactions of the immediate type could be characterized by the impedance technique, and the instrument is a candidate tool for evaluation of the efficacy of antihistamines.…”
Section: Wheal Flare Reactionsmentioning
confidence: 88%
“…Nyren et al performed several tests based on this idea. The method had already been applied to the study of eczema and skin reactions, but its application to allergic wheals had not yet been carried out.…”
Section: Methods and Systems For Automatic Wheal Measurementmentioning
confidence: 99%